2023
DOI: 10.1097/j.pain.0000000000002950
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous nerve fiber and peripheral Nav1.7 assessment in a large cohort of patients with postherpetic neuralgia

Michael Fetell,
Manon Sendel,
Thomas Li
et al.

Abstract: The mechanisms of pain in postherpetic neuralgia (PHN) are still unclear, with some studies showing loss of cutaneous sensory nerve fibers that seemed to correlate with pain level. We report results of skin biopsies and correlations with baseline pain scores, mechanical hyperalgesia, and the Neuropathic Pain Symptom Inventory (NPSI) in 294 patients who participated in a clinical trial of TV-45070, a topical semiselective sodium 1.7 channel (Nav1.7) blocker. Intraepidermal nerve fibers and subepidermal Nav1.7 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Previous research has demonstrated ipsilateral SFN among cohorts of patients with PHN, as well as other innervation alterations; however, not all patients with PHN show ipsilateral fiber loss. 24,56,59 Therefore, for this study, we used an enriched cohort of PHN patient biopsies that were known to fit the prevailing notion that a loss of IENF occurs on the ipsilateral (pain) side compared with contralateral (nonpain). The following criteria were used for the selection of the innervation-standardized PHN patient cohort biopsies used for this research study from review of the 271 total PHN patient tissue database:(1) An initial study VAS score ≥5.5 (average VAS score for the 271 patient study was 5.5).(2) A contralateral IENF density that was within one standard deviation of the 271 patient study average (10.3 fibers/mm length of epidermis).(3) A 30% to 50% reduction of the ipsilateral IENF density compared with contralateral IENF density.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has demonstrated ipsilateral SFN among cohorts of patients with PHN, as well as other innervation alterations; however, not all patients with PHN show ipsilateral fiber loss. 24,56,59 Therefore, for this study, we used an enriched cohort of PHN patient biopsies that were known to fit the prevailing notion that a loss of IENF occurs on the ipsilateral (pain) side compared with contralateral (nonpain). The following criteria were used for the selection of the innervation-standardized PHN patient cohort biopsies used for this research study from review of the 271 total PHN patient tissue database:(1) An initial study VAS score ≥5.5 (average VAS score for the 271 patient study was 5.5).(2) A contralateral IENF density that was within one standard deviation of the 271 patient study average (10.3 fibers/mm length of epidermis).(3) A 30% to 50% reduction of the ipsilateral IENF density compared with contralateral IENF density.…”
Section: Methodsmentioning
confidence: 99%
“…Deidentified PHN human research tissue for this study was collected before any drug treatments from an unrelated clinical study ( ClinTrials.gov NCT02365636/TEVA Pharmaceuticals) where each subject provided a contralateral and ipsilateral biopsy from the same thoracic dermatome. 24 All patients fully consented to the deidentified use of biopsy material in additional basic research projects under the direction of Integrated Tissue Dynamics, LLC (INTiDYN). Previous research has demonstrated ipsilateral SFN among cohorts of patients with PHN, as well as other innervation alterations; however, not all patients with PHN show ipsilateral fiber loss.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations